Notary Protocols in Indonesia: Position, Urgency, and the Rule of Law - Khairunnisa, Azzahra Kamiliya (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2025)
This research addresses the critical yet under-regulated area of notary protocol submission and management within the Indonesian legal system. Despite the Notary Position Law (UUJN), a significant legal vacuum persists regarding implementation procedures, leading to practical obstacles such as lost or incomplete protocols and refusal of acceptance. This deficiency undermines legal certainty, hinders administrative efficiency, and risks harm to involved parties. This study offers a novel in-depth analysis of these shortcomings and proposes concrete, comprehensive regulatory solutions to streamline submission and management processes. The research contributes by providing specific recommendations aimed at enhancing legal certainty, preventing administrative issues, and ultimately strengthening the notary's role in upholding the validity and security of legal transactions. The urgent need for clearer regulations is underscored by the current practical impediments and their potential for broader legal disruption.